Analysis of Knowledge, Attitude, Employee Action in the Use of Personal Protective Equipment (PPE) with Work Accidents - Nur Aini Fatimah; Nurwijayanti Nurwijayanti; Siti Farida (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
One of the causes of workplace accidents is the lack of awareness of the use of personal protective equipment for workers in the workplace. One of the ways to prevent workplace accidents is to require personal protective equipment (PPE) that meets the requirements, namely: comfort in use, does not hinder the work process, and provides effective protection against types of hazards. The objective of this research was to analyze the knowledge, attitudes, actions of employees in the use of personal protective equipment with work accidents at PT. Bisi International, Tbk., Tulungrejo Pare Kediri. The design of this research was quantitative method of correlation(correlation study) and approach cross sectional. The sampling technique was use Proportionate Stratified Random Sampling with a sample of 96 respondents, the processing unit and engineering unit at PT. Bisi International, Tbk., Tulungrejo Pare Kediri. The results of the research data were analyzed by ordinal regression test. The results of statistical analysis with ordinal regression showed that there was no relationship between knowledge, attitudes, actions of employees in the use of personal protective equipment (PPE) with the occurrence of work accidents at PT. Bisi International, Tbk., Tulungrejo Pare Kediri. The company must play an active role in giving awareness to employees about the importance of adhering to procedures and complying with the regulations in the use of personal protective equipment while working